Notes to Philosophy 167: Class 10 -- Huygens and the Beginnings of Rational Mechanics -- Part 11. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Empirical Evidence for the Overall Theory -- Background: Ideal versus Real Pendulums.; Generally corresponds to the video segment: Class 10, Part 11.